Cyber Security Assemblages: A Framework for Understanding the Dynamic and Contested Nature of Security Provision - Collier, Jamie (2018)
In the context of globalisation and privatisation, an emerging body of literature has applied the concept of an ‘assemblage’ to international relations and security studies. This article will argue that an assemblage framework provides the best means for understanding the complex configuration of cyber security actors, given that contemporary cyber security practices do not conform to the traditional public-private and global-local distinctions used in security studies and International Relations literature. With the configuration of cyber security actors, and the relationships between them in constant flux, an assemblage framework provides a means for understanding the contested, dynamic and diachronic nature of contemporary cyber security provision. While the concept of security assemblages is favoured in this article, the process and context in which the term has traditionally been used cannot be blindly imposed on the issue of cyber security. This article will therefore propose a different model of how cyber security assemblages have developed and explain the implications this has on contemporary security dynamics.